Systemy zarządzania w perspektywie mechanizmów grupowych - Barabasz, Adela (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
The article shows applying knowledge of the phenomena and mechanisms governing groups from the point of view of group analysis, general systems theory, the concept of Michael Hammer, deep and surface systems, and also the idea of organizational personality. The author attempts to show that viewing an organization through the prism of the mechanisms of personality function will not only help in understanding organization better, but also in designing management systems more efficiently. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 297-304